A Misleading Trismus - A. Galzerano; E. Sabatini; A. De Monte; D. Durì (Case Reports in Critical Care)
We report the case of a 73-year-old women admitted to ICU with a diagnosis of tetanum supported by a mild trismus and treated with potentially unsafe drugs until the correct diagnosis was made.